Morphological disparity of extant and extinct pinaceous ovulate cones: How many cones are enough?. Issue 9 (5th September 2022) - De Brito, Léa; Fischer, Valentin; Prestianni, Cyrille
Abstract: Premise: The expansion of Pinaceae during the Cretaceous is exemplified by the numerous ovulate cone taxa found in western Europe and North America. The Belgian Wealden facies deposits have delivered hundreds of exceptionally well‐preserved yet isolated pinaceous ovulate cones; these cones were placed by convention within form‐genera. Ten species have been described in Belgium, representing about 20% of the known fossil record of this period. However, the validity of these taxa is questionable because their intra‐ and interspecific variabilities have never been thoroughly studied. Moreover, quantifying the expansion of Pinaceae in terms of morphospace occupation is desirable to reveal the dynamics of this critical radiation. Methods: We used linear and geometric morphometry to quantify the shape of the extensive sample of Cretaceous cones of Belgium. These methods were also applied to extant pinaceous species to compare the morphological disparity of Cretaceous assemblages against those of today in selected ecosystems. We used ordination methods (PCA) to visualize morphospace occupation and test for species delineation. Results: The morphological disparity was not higher in fossil species than in extant species we sampled. Both morphological approaches confirmed that the species Pityostrobus andraei presents high morphological variability. Our resampling tests indicate that ovulate cone morphological variability can be satisfactorily quantified with as few as 15 specimens. Conclusions: The methodology used here is relevant for quantifying both the variability and the diversity of many fossil assemblages, paving the way for a more robust evaluation of Cretaceous pinaceous diversity.